Protecting the 2020 Census: A new framework is being used to secure the 2020 U.S. Census from database reconstruction attacks. - Kugler, Logan (Communications of the ACM, 2019)
The article discusses the database security frameworks developed by the U.S. Census Bureau to prevent database reconstruction attacks of the 2020 U.S. Census. An overview of the Census Bureau's use of differential privacy, a statistic method, in order to prevent cyberattacks on the U.S. 2020 Census database, including Bureau associate director John Abowd's role in this regard, is provided.